OPTIMASI PROSES PRODUKSI BIODIESEL DARI MINYAK KELAPA SAWIT DAN JARAK PAGAR DENGAN MENGGUNAKAN KATALIS HETEROGEN KALSIUM OKSIDA - Murti, Galuh Wirama; Rahmawati, Nurdiah; Heriyanti, Septina Is; Hastuti, Zulaicha Dwi (Jurnal Energi dan Lingkungan (Enerlink), 2015)
Production of biodiesel has been conducted through several processes such as esterification andtransesterification by homogeneous catalyst in which use either acidic or alkaline substances.Homogeneous catalysts have some negative impacts to the environment, because technically itrequires further treatment process such as washing. Therefore, the use of heterogeneouscatalysts is proposed to be best way to overcome this problem. The advantages of heterogeneouscatalysts are not only for its ease in recovery but also for its reusability. Moreover, it isenvironmentally friendly and cheap which only undergo a single process of transesterification.Calcium oxide is well-known as one of heterogeneous catalysts. It were activated by pretreatmentwith methanol and then it was continued by transesterification reaction. The optimal reactiono conditions were obtained at temperature 60 C, atmospheric pressure, and 4 h reaction time.Calcium oxides shows good activity in transesterification reaction using either palm or jatropha oil.The highest conversion of palm oil is approximately 62,51% within catalyst 3% by weight oil,whereas jatropha oil is approximately 53.10 % within catalyst 10% by weight oil. The regeneratedcatalyst shows low catalytic activity which is indicated by small presence of methyl ester in theproduct.Key words : biodiesel, heterogen catalyst, calcium oxide, palm oil, jatropha oil